Is obesity rather than the dietary supplement used for weight reduction the cause of liver injury?. Issue 4 (6th June 2018) - Teschke, Rolf; Wolff, Albrecht; Eickhoff, Axel; Danan, Gaby
Abstract : Acute liver injury has been attributed to dietary supplements (DS) used for weight loss, but their causal role was much questioned, and obesity as an alternative cause of the liver injury remained unclear. A comprehensive search of the Medline database was conducted with terms that included "DS, " "liver injury, " "obesity, " "obesity‐related liver diseases, " and "nonalcoholic steatohepatitis." For each term, we focused on the first 50 publications. We undertook a manual search to identify additional reports. Underlying liver diseases and other health issues are common in patients taking DS for weight reduction. These include obesity or morbid obesity, as well as complex metabolic disorders complicated by excess morbidity and mortality due to associated liver diseases. Among these are nonalcoholic fatty liver disease with potential progression to nonalcoholic steatohepatitis and cirrhosis, often classified as cryptogenic with a rare risk of hepatocellular carcinoma. With the exception of hepatocellular carcinoma, these obesity‐related liver diseases were observed to varying degrees in patients, and some even required a liver transplant. This raises the question whether the liver injury that occurred in these patients is due to DS consumed for weight loss or to the underlying obesity‐related liver diseases. This analysis showed that, in many instances, the causal role of obesity has been neglected. Obesity‐associated liver diseases should be considered as differential diagnosis of liver injury in obese patients using DS. Abstract : Liver injury in obese patients using dietary supplements for weight reduction must be assessed for the cause of liver injury. Differential diagnoses include obesity‐related liver disease, which is much more common, or dietary supplement‐related liver injury, a rare event. The use of RUCAM to assess causality is recommended.